2014
DOI: 10.1111/hex.12221
|View full text |Cite
|
Sign up to set email alerts
|

The development and initial validation of a clinical tool for patients' preferences on patient participation – The 4Ps

Abstract: Aims To report on the development and initial testing of a clinical tool, The Patient Preferences for Patient Participation tool (The 4Ps), which will allow patients to depict, prioritize, and evaluate their participation in health care.Background While patient participation is vital for high quality health care, a common definition incorporating all stakeholders' experience is pending. In order to support participation in health care, a tool for determining patients' preferences on participation is proposed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(112 citation statements)
references
References 37 publications
6
106
0
Order By: Relevance
“…More recently, a measure of patient participation in nursing captured four domains; having dialogue with healthcare staff, sharing knowledge, partaking in planning and managing self‐care (Eldh et al . ). In addition, a conceptual model used in a 2016 review of instruments measuring patient participation in health care identified three core requirements; patients having critical self‐knowledge, shared decision‐making and self‐care/autonomy (Phillips et al .…”
Section: Introductionmentioning
confidence: 97%
“…More recently, a measure of patient participation in nursing captured four domains; having dialogue with healthcare staff, sharing knowledge, partaking in planning and managing self‐care (Eldh et al . ). In addition, a conceptual model used in a 2016 review of instruments measuring patient participation in health care identified three core requirements; patients having critical self‐knowledge, shared decision‐making and self‐care/autonomy (Phillips et al .…”
Section: Introductionmentioning
confidence: 97%
“…and listen to what they have to say [31]. Consequently, communication is an essential facilitator of patients' participation in DP.…”
Section: Discussionmentioning
confidence: 99%
“…As patient participation connotes a variety of attributes, contemplating the concept can be challenging, unless means are provided. The Patient Preferences for Patient Participation (the 4Ps) is a novel tool, based on comprehensive reviews of policies, health terminology, and classifications, along with studies of how patients and professionals define the concept and how and when it is facilitated . The 4Ps structure and content is outlined in detail in Table .…”
Section: Providing For Patient Participationmentioning
confidence: 99%
“…As suggested, these sections can serve as a basis for dialogues on and plans for health care interventions, in addition to follow‐ups, and/or for evaluation purposes. Considering that patients' preferences for participation may vary with, for example, age, gender, current situation and/or symptoms and their duration, and type of health care contact, the 4Ps has been suggested promising . Yet, its relevance has been primarily established for adults in contact with acute, long‐term, or primary care, but further studies are required to validate its appropriateness, for example, for people with cognitive deficits.…”
Section: Providing For Patient Participationmentioning
confidence: 99%